Anti-inflammatory effects of orally administered glucosamine oligomer in an experimental model of inflammatory bowel disease. (22nd January 2015) - Azuma, Kazuo; Osaki, Tomohiro; Kurozumi, Seiji; Kiyose, Masatoshi; Tsuka, Takeshi; Murahata, Yusuke; Imagawa, Tomohiro; Itoh, Norihiko; Minami, Saburo; Sato, Kimihiko; Okamoto, Yoshiharu
Highlights: The anti-inflammatory activities of glucosamine oligomer (COS) in IBD model. COS inhibit colonic inflammation and reduced tissue injury. COS suppress activations of NF-κB, COX-2 and iNOS. COS are candidate anti-inflammatory functional foods for IBD patients. Abstract: Anti-inflammatory effects of oral administration of the glucosamine oligomers (chito-oligosaccharides: COS) were evaluated in an experimental model of inflammatory bowel disease (IBD). Oral administration of COS improved shortening of colon length and tissue injury (as assessed by histology) in mice. Oral administration of COS inhibited inflammation in the colonic mucosa by suppression of myeloperoxidase activation in inflammatory cells, as well as activation of nuclear factor-kappa B, cyclooxygenase-2, and inducible nitric oxide synthase. Oral administration of COS also reduced serum levels of pro-inflammatory cytokines (tumor necrosis factor-α and interleukin-6). Moreover, it prolonged survival time in mice. These data suggest that COS have anti-inflammatory effects in an experimental model of IBD, and could be new functional foods for IBD patients.